2005
DOI: 10.1021/ja0508469
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Aerobic Synthesis of Nanocrystalline Magnetite

Abstract: The synthesis of iron oxide nanoparticles of the predominantly magnetite phase by the reaction of aqueous iron complexes with the bacterium, Actinobacter spp., is described. This reaction occurs at room temperature and under aerobic conditions, resulting in the formation of superparamagnetic magnetite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(73 citation statements)
references
References 15 publications
1
71
0
1
Order By: Relevance
“…[10][11][12] Inspired by the magnetosensing behaviors in nature, artificial magnetic-field perception could possibly be achieved by fabricating a kind of micro-/nanostructure assembled by superparamagnetic magnetite nanoparticles, which requires synthesis of nanoparticles and fabrication of anisotropic-magnetization structures. Recent advances in colloidal chemistry have provided many potential protocols for synthesis of superparamagnetic-magnetite nanoparticles with controlled sizes and morphologies, [13][14][15] thus the key challenges for realizing…”
Section: Doi: 101002/adma201601609mentioning
confidence: 99%
“…[10][11][12] Inspired by the magnetosensing behaviors in nature, artificial magnetic-field perception could possibly be achieved by fabricating a kind of micro-/nanostructure assembled by superparamagnetic magnetite nanoparticles, which requires synthesis of nanoparticles and fabrication of anisotropic-magnetization structures. Recent advances in colloidal chemistry have provided many potential protocols for synthesis of superparamagnetic-magnetite nanoparticles with controlled sizes and morphologies, [13][14][15] thus the key challenges for realizing…”
Section: Doi: 101002/adma201601609mentioning
confidence: 99%
“…yielded two new proteins that synthesize magnetite nanoparticles. The biotransformation of ferri-/ferrocyanide complexes into magnetite was dependent on the proteins secreted by this bacterium [34]. Incubating Actinobacter spp.…”
Section: Cobalt Oxide (Co3o4) Nanocrystalsmentioning
confidence: 99%
“…with a ferricyanide/ferrocyanide mixture for 24 or 48 h resulted in quasi-spherical magnetite nanoparticles (10-40 nm) and cubic nanoparticles (50-150 nm), respectively. The nanoparticles were stable in aqueous solutions for several weeks because of the biomolecules secreted by the bacterium and were superparamagnetic at room temperature [34]. The mycelia of acidophillic fungi, Verticillium sp.…”
Section: Cobalt Oxide (Co3o4) Nanocrystalsmentioning
confidence: 99%
“…In another study, Riddin et al demonstrated cell-free, cell-soluble protein extract from a consortium of sulphatereducing bacteria in the biosynthesis of geometric Pt(0) nanoparticles [ 34 ]. Similarly, Bharde et al demonstrated magnetite nanoparticle synthesis by Actinobacter , a nonmagnetotactic bacterium, using iron precursors under aerobic conditions [ 35 ]. While earlier studies were very slow (about 1 week) and required strictly anaerobic conditions, this study tends to ease the required process control, one of the several benefi ts of biogenic synthesis.…”
Section: Bacteria and Yeastmentioning
confidence: 99%